Impact of Informal School Language Policies on Indigenous Languages in a Multilingual Context - Kshetry , Nixan Thapa; Poudel, Tikaram (Nepalese Linguistics, 2025)
The duration of students’ exposure to and use of a language in school significantly influences their future linguistic competence, regardless of the language studied (Allen, 2010; Swain & Watanabe, 2013). Nevertheless, researchers’ observations and experiences concerning school language policy and multilingualism suggest that the situation of local or indigenous language learners in Nepali schools is often marginalized. We collected the data for this study in two schools of Madhesh Province, Nepal, following the principles of the ethnographic research method. We analyzed the data using a thematic analysis approach. The findings underscore the need to prioritize endangered languages by investigating the types of language policies implemented in Nepali schools and exploring school leaders’ perceptions on indigenous and local languages, with particular attention to the two case schools examined.